Strategi komunikasi politik elit NU Pada pilkada lombok tengah 2020 (Studi atas keterlibatan elit NU dalam tim pemenangan paslon Maiq Meres) - Sutangga, Jhoni; Kadri, Kadri; Fahri, Moh. (Lembaga Penelitian dan Pendidikan Mandala, 2023)
The involvement of NU organizational elites can be seen from the role, contribution and political communication strategies they played during the 2020 regional elections in convincing the electorate at the grassroots level. In the regional elections in Central Lombok district in 2020, the political phenomenon that was visible before the voting public was related to the involvement of the Central Lombok NU elite in winning the Lalu Pathul Bahri Candidate Pair - HM Nursiah or the Maiq Meres candidate pair. This research is participatory field research with a descriptive qualitative approach. Data collection was carried out by means of observation, interviews and documentation. The research process was carried out intensively for two months involving informants consisting of main informants and supporting informants regarding the winning of regional head candidates Lalu Pathul Bahri-HM Nursiah. This study found that the Central Lombok district NU elite played an active role as a medium, or media for political communication, the pair of candidates for regent and candidate for deputy regent of Central Lombok Pathul Bhari and HM. Nursiah. The Central Lombok NU elite took part in visiting the electorate, both personally and institutionally. The communication strategy used by the NU elite to convey political messages is to maximize the role of the organizational network, the network of NU teachers, as well as NU's amaliyah activities, which are driven to support pairs of regional head candidates supported by NU.